2019
DOI: 10.1093/jas/skz005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complexed trace minerals on cumulus-oocyte complex recovery and in vitro embryo production in beef cattle1,2

Abstract: The objective of this experiment was to evaluate the impact of complexed trace mineral supplementation on ovum pick-up (OPU) and in vitro embryo production in lactating beef cows. Thirty days prior to fixed-time artificial insemination (FTAI; day −30), 68 postpartum cows were stratified by BW, BCS, and parity before being randomly assigned to 10 pens of either a treatment (TRT; n = 5) or a control (CNT; n = 5) group. Each group received a weekly mineral supplement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Similarly, dietary trace mineral supplementation had no effect on the number of ova/embryos recovered from beef heifers, or the number of corpus lutea on the ovaries, indicating trace mineral supplementation likely does not impact ovulation [ 8 ]. While follicular activity may not be impacted by trace minerals, the oocyte appears to be susceptible to maternal dietary supplementation, as supplementation prior to ovum pick-up (OPU) increased the number of cumulous-oocyte complexes (COC) collected and increased oocyte maturation rates during in vitro culture [ 9 ].…”
Section: Maternal Production and Healthmentioning
confidence: 99%
“…Similarly, dietary trace mineral supplementation had no effect on the number of ova/embryos recovered from beef heifers, or the number of corpus lutea on the ovaries, indicating trace mineral supplementation likely does not impact ovulation [ 8 ]. While follicular activity may not be impacted by trace minerals, the oocyte appears to be susceptible to maternal dietary supplementation, as supplementation prior to ovum pick-up (OPU) increased the number of cumulous-oocyte complexes (COC) collected and increased oocyte maturation rates during in vitro culture [ 9 ].…”
Section: Maternal Production and Healthmentioning
confidence: 99%
“…Previous research demonstrated that supplementing organic complexed trace minerals improved reproductive performance in dairy cattle, such as decreased interval to first estrus and increased pregnancy rates ( Uchida et al, 2001 ; Griffiths et al, 2007 ). In beef cows, supplementing organic complexed Co, Cu, Mn, and Zn resulted in greater number of culturable oocytes and transferable embryos from in vitro fertilization compared with cohorts receiving sulfate sources ( Dantas et al, 2019 ). These latter results may help explaining the hastened puberty attainment of heifers from AAC cows in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Organic trace mineral supplementation to dairy cows significantly increased milk production, milk fat yield, and milk protein yield compared to inorganic trace mineral supplemented cohorts [ 44 ]. Previous research has demonstrated supplemented organic complexed trace minerals improved reproductive performance in cattle, decreasing interval to first estrus and increasing pregnancy rates [ 45 , 46 ], as well as resulting in improved in vitro embryo production efficiency [ 47 ]. A meta-analysis by Rabiee et al [ 48 ] reported that lactating dairy cows supplemented with organic-complexed trace minerals have greater milk yield, fewer days open, and require fewer services per conception compared with inorganic supplemented cohorts.…”
Section: Developmental Programmingmentioning
confidence: 99%
“…The role of trace mineral source on reproductive performance is complex, especially given the plethora of processes each element participates in, and the essentiality of each in all aspects of development [ 32 ]. Previous research demonstrated lactating beef cows supplemented with organic Co, Cu, Mn, and Zn yielded a greater number of culturable oocytes and transferable embryos compared with cohorts receiving sulfate sources of the same elements [ 47 ]. Primordial germs cells within the developing ovary actively utilize machinery and enzymes against reactive oxygen species (ROS) to maintain cell integrity [ 96 ], and increased antioxidant enzyme activity and decreased ROS production during germ cell development results with trace mineral supplementation [ 97 , 98 ].…”
Section: Supplementing Organic-complexed Trace Minerals Mid- To Late-gestationmentioning
confidence: 99%